Implementasi Pendidikan Inklusi di Sekolah Dasar: Tantangan Dan Strategi Efektif - Kesti Anggreani; Nur Ahsana Tafsira; Trisna Febriyani; Elsha Syafitri (Lembag, 2024)
This study aims to identify challenges and formulate effective strategies in implementing inclusive education in primary schools. A qualitative approach with descriptive methods was used to gain an in-depth understanding of the issue. Data were collected through observation, in-depth interviews and documentation involving school principals, classroom teachers, special mentor teachers and parents. The research findings show that the main challenges in implementing inclusive education are the lack of teachers' understanding and skills, limited facilities and infrastructure and resistance from parents. To overcome these challenges, several strategies were proposed, including continuous professional development and training for teachers, improving school facilities and infrastructure, and socialising and educating parents and communities. The case study of SD Negeri 13 Pandeglang shows that collaboration between the school, government and community can improve the acceptance and success of inclusive education. Support from the government in the form of clear policies and provision of adequate resources is also very important. In conclusion, with the right strategies and adequate support, inclusive education can be effectively implemented in primary schools, benefiting all students, including those with special needs.